The Transformation of Islamic Education in Pesantren: Integrating Digital Marketing within the Global EdTech Ecosystem - Uryatul hikmah; Yusril Ihza Saputra; Hafidatun Nabila; Aminullah Aminullah; Moh. Holidi; Badrul Mudarris (Universitas Nurul Jadid, 2025)
Study This aim For analyze modern Islamic boarding school rebranding strategy in maintain identity tradition while adopt technology global education (EdTech) for strengthen position in the digital education market. Research This use approach qualitative descriptive with studies cases in some superior modern Islamic boarding school. Data collected through interview deep with manager Islamic boarding school, observation activity digital marketing, as well as analysis content on social media platforms and official websites. Research This show that modern Islamic boarding schools are rebranding through specific market segmentation, use visual content that combines ethics Islamic with modern aesthetics , as well as utilization of EdTech platforms for learning distance far. Strategy This succeed change perception public from institutions traditional become institutions relevant futuristic with need global industry without remove mark originality Islamic boarding school. In general practical, research This give guide for institutions education religion based for do measurable digital transformation. In theoretical, results This enrich literature about management marketing education in face disruption technology in the global era